Liver and kidney preservation by perfusion. - St Peter, S; Imber, C; Friend, P (2002)
The clinical boundaries of transplantation have been set in an era of simple cold storage. Research in organ preservation has led to the development of flush solutions that buffer the harsh molecular conditions which develop during ischaemia, and provide stored organs that are fit to sustain life after transplantation. Although simple and efficient, this method might be reaching its limit with respect to the duration, preservation, and the quality of organs that can be preserved. In addition, flush preservation does not allow for adequate viability assessment. There is good evidence that preservation times will be extended by the provision of continuous cellular substrate. Stimulation of in-vivo conditions by ex-vivo perfusion could also mean that marginal organs will be salvaged for transplantation. Perfusion will also allow for assessing the viability of organs before transplantation in a continuous fashion. The cumulative effect of these benefits would include expansion of the donor pool, less risk of primary non-function, and extension of the safe preservation period. Use of non-heart-beating donors, international organ sharing, and precise calculation of the risk of primary organ failure could become standard.